2023
DOI: 10.1371/journal.pone.0275412
|View full text |Cite
|
Sign up to set email alerts
|

Drought adaptability of different subspecies of tetraploid wheat (Triticum turgidum) under contrasting moisture conditions: Association with solvent retention capacity and quality-related traits

Abstract: Few prior efforts have been made to investigate the genetic potential of different subspecies of Triticum turgidum for drought tolerance and their quality-related traits compared with common wheat (Triticum aestivum) and to identify the association among agronomic, micronutrients, and quality-related traits, especially under climate change conditions. In this research, grain quality, technological properties of flour, and some agronomic traits were studied in 33 wheat genotypes from six different subspecies of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Recent research using the genetic and phenotypic analysis of wheat spike and kernel traits revealed long-term and geographic trends resulting from the breeding process [22]. Furthermore, small-effect QTL contributes to the quantitative inheritance of traits and is supported by genomic prediction [23].…”
Section: Influence Of Genotype On Wheat Yieldmentioning
confidence: 99%
“…Recent research using the genetic and phenotypic analysis of wheat spike and kernel traits revealed long-term and geographic trends resulting from the breeding process [22]. Furthermore, small-effect QTL contributes to the quantitative inheritance of traits and is supported by genomic prediction [23].…”
Section: Influence Of Genotype On Wheat Yieldmentioning
confidence: 99%